2024
DOI: 10.1371/journal.pclm.0000361
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal trends and variability of rainfall across agro-ecologies in East Guji Zone, Southeast Ethiopia

Menbere Sahilu,
Solomon Tekalign,
Yimer Mohammed
et al.

Abstract: Distribution and trends of rainfall reveal spatial and temporal variability that have a paramount effect on the life and livelihood of small-holder farmers. This study aimed to analyze spatial variability and temporal trends of rainfall distribution across the three Agro-Ecological Zones (AEZs) of East Guji. Time series gridded daily rainfall data (1990–2020) were collected from the Ethiopian Meteorological Institution. Different descriptive statistics, trend tests: Man Kendal and Sen’s slope estimator, Invers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
2
1
Order By: Relevance
“…In the short rainy Belg season, moderate variability (25.77 %) was observed in the south-central midland AEZ, whereas the northeast highland AEZ had higher variability (46.25 %). This finding contrasts with Sahilu et al [ 57 ] findings, who identified moderate rainfall variability (CV <30 %) in the highland areas, with values of 28 %, 30 %, and 29 % during the spring, summer, and autumn seasons, respectively. Notably, Birara [ 39 ] reported conflicting results, indicating that regions with low annual rainfall exhibited high rainfall coefficient of variability.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…In the short rainy Belg season, moderate variability (25.77 %) was observed in the south-central midland AEZ, whereas the northeast highland AEZ had higher variability (46.25 %). This finding contrasts with Sahilu et al [ 57 ] findings, who identified moderate rainfall variability (CV <30 %) in the highland areas, with values of 28 %, 30 %, and 29 % during the spring, summer, and autumn seasons, respectively. Notably, Birara [ 39 ] reported conflicting results, indicating that regions with low annual rainfall exhibited high rainfall coefficient of variability.…”
Section: Resultscontrasting
confidence: 99%
“…Negative anomalies indicate a potential decline in stream flows and groundwater levels, posing a significant danger to irrigated agriculture and related industries [ 93 ]. According to Sahilu et al [ 57 ], short-term fluctuations are caused by changes in El Niño (ENSO), Indian Ocean dipole (IOD), and differential warming over the Indian Ocean.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation